Some Issues in the Design of Monetary Instruments for the Operation of European Economic and Monetary Union - Hilbers, Paul (IMF Working Papers; Working Paper ;, 1997)
The European Monetary Institute has been working with national central banks of the European Union (EU) to prepare instruments for the operation of monetary policy in Stage 3 of European Economic and Monetary Union. Several publications describing the proposed arrangements have been issued. This paper briefly summarizes the arrangements and identifies some areas in which important decisions still have to be made or refinements introduced-including the choice of counterparties in fine-tuning open market operations; the design of reserve requirements; the signaling function of monetary operations; and payment system relationships with non-EMU participants in the EU.